A Review on Micro Formings - Amin, Teyfouri; Milad, Ahmadi; Erfan, Shamsaddini lori; Sorooshian, Shahryar (Canadian Centerof Science and Education, 2015)
Nowadays, there are increasing demand on micro-systems, micro products/components and micro-devices. Thus, the role of micro manufacturing in all aspects of modern industry is taken for granted. Then, typical processes in micro manufacturing are discussed. Furthermore, one of the most widespread micro-manufacturing processes in deforming processes is micro forming that is presented in this paper. Finally, besides continuing effort in developing micro forming, this paper strives to analyze systematically the key methods of stamping, bending, forging and deep drawing processes and their prominent issues.